2019
DOI: 10.3390/nano9050739
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Optical Properties of Hyperbolic Metamaterials by Controlling the Volume Fraction of Metallic Nanorods

Abstract: Porous films of anodic aluminum oxide are widely used as templates for the electrochemical preparation of functional nanocomposites containing ordered arrays of anisotropic nanostructures. In these structures, the volume fraction of the inclusion phase, which strongly determines the functional properties of the nanocomposite, is equal to the porosity of the initial template. For the range of systems, the most pronounced effects and the best functional properties are expected when the volume fraction of metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Thus, a decrease in the density of active electrodes could be more appropriate because of the decrease in electric double layer charging current and, as a consequence, the growth of the signal-to-noise ratio. A controlled decrease in the active nanoelectrodes in the array can be achieved by modification of the AAO structure and artificial pore branching [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a decrease in the density of active electrodes could be more appropriate because of the decrease in electric double layer charging current and, as a consequence, the growth of the signal-to-noise ratio. A controlled decrease in the active nanoelectrodes in the array can be achieved by modification of the AAO structure and artificial pore branching [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Simulations of the permittivity components within the effective medium model show that the spectral positions of these resonances coincide with the pole of the effective  and zero of   components, respectively [21]. Variation of the metal volume fraction and the length of nanorods allows us to tune the spectral position of the ENZ point [22]. Moreover, strong HMM dispersion in the vicinity of the ENZ and ENP points leads to giant optical birefringence unattainable in natural media, whereas it is rather promising for applications in polarization converters [16,23].…”
Section: Introductionmentioning
confidence: 93%
“…Today, porous AAO films find numerous applications as membranes, 2−4 porous supports, 5,6 templates, 7−10 sensors, 11−13 photonic crystals, 14,15 and metamaterials. 16,17 It has been found that increasing the degree of pore ordering improves the functional properties of AAO substantially. 18−21 AAO with highly ordered structure forms if anodizing is performed under kinetic or diffusion control of the electrode reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the discovery of anodic aluminum oxide (AAO) with an ordered honeycomb-like structure, aluminum anodizing in acidic electrolytes is widely used in nanotechnology. Today, porous AAO films find numerous applications as membranes, porous supports, , templates, sensors, photonic crystals, , and metamaterials. , It has been found that increasing the degree of pore ordering improves the functional properties of AAO substantially. AAO with highly ordered structure forms if anodizing is performed under kinetic or diffusion control of the electrode reaction. , …”
Section: Introductionmentioning
confidence: 99%